The daytime serials of television, 1946 - 1960 - Cox, Jim 1939- (McFarland, 2010)
"This history of 'golden age' soaps begins with an overview of earlier serialized entertainments that set the stage for the televised daytime soap. An analysis of early TV soap stars, personnel and production follows. Appendices include chronological and alphabetical directories of period daytime serials and rankings, actors and actresses, announcers and sponsors"--Provided by publisher